Acute Compartment Syndrome of the Lower Leg after Coronary Artery Bypass Grafting: A Silent but Dangerous Complication - te Kolste, Henryk Jan; Balm, Ron; de Mol, Bas (The Thoracic and Cardiovascular Surgeon, 2015)
Background Acute compartment syndrome (ACoS) is a serious, limb-threatening condition, but ACoS after coronary artery bypass grafting (CABG) is rare. ACoS is diagnosed with the help of typical symptoms, but due to the use of analgesics in a postoperative setting, these symptoms may vary. Identifying risk factors for ACoS after CABG could reduce the risk of developing this complication.Methods We describe the clinical presentation, diagnosis, and management of five cases of ACoS arising from CABG procedures at our institution during the last 5 years. We also review all cases found in literature about this complication.Discussion Both systemic and local factors may contribute to ACoS of the lower leg. These factors include increased microvascular permeability caused by cardiopulmonary bypass (CPB), the use of cardiac-assist devices causing arterial occlusion and reperfusion injury, diminished arterial blood flow in patients with peripheral vascular disease due to lithotomy position and the use of elastic bandages and local trauma and hematoma formation due to the harvesting of the greater saphenous vein (GSV).Conclusion To prevent this serious complication, we advise to pay extra attention to the patients with a greater risk. Hemostasis after venectomy in CABG surgery is mandatory, especially in the endoscopic harvesting of the GSV. Elastic bandages should be applied after weaning from CPB. Elevated creatine phosphokinase values may indicate ACoS. When suspicion arises, intracompartmental pressure measurement is the preferred tool for early recognition and diagnosis. To prevent irreversible, extensive tissue damage and permanent disability fasciotomy must be performed immediately after the diagnosis is made.
Keywords: coronary artery bypass grafts surgery; CABG; anesthesia; cardiopulmonary bypass; CPB; IABP; intensive care; postoperative care